2015
DOI: 10.3413/nukmed-0751-15-06
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic toxicity of radium-223 in patients with high skeletal tumour burden

Abstract: Close follow-up of haematopoietic indices and, in case of toxicity, early termination of therapy is in particular necessary in late stage disease where limited bone marrow reserve is likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Dose-limiting toxicities, however, are usually well described. For [ 225 Ac]Ac-PSMA-617, for instance, the destruction of the salivary glands represents the dose-limiting organ [34], whereas for [ 223 Ra]RaCl 2 haematotoxicity can lead to premature termination of the therapy [113]. Furthermore, the high LET radiation might lead to cancer induction and genetic diseases [112,114,115].…”
Section: Atomic Nanogenerators In Modern Cancer Managementmentioning
confidence: 99%
“…Dose-limiting toxicities, however, are usually well described. For [ 225 Ac]Ac-PSMA-617, for instance, the destruction of the salivary glands represents the dose-limiting organ [34], whereas for [ 223 Ra]RaCl 2 haematotoxicity can lead to premature termination of the therapy [113]. Furthermore, the high LET radiation might lead to cancer induction and genetic diseases [112,114,115].…”
Section: Atomic Nanogenerators In Modern Cancer Managementmentioning
confidence: 99%
“…Most single-institution studies (n = 9/25, 36%) originated from the United States; moreover, most of the multi-institutional studies included an American center (n = 6/9, 67%) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Five studies originated from Germany [ 23 , 24 , 25 , 26 , 27 ], four from Sweden [ 28 , 29 , 30 , 31 ], and six from Japan [ 32 , 33 , 34 , 35 , 36 , 37 ]. Information about patient number, acquisition technique, type of employed isotope (when applicable) and method of computational analysis were obtainable from all studies.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the ALSYMPCA trial, in which the bone scan response to treatment with 223 Ra was not evaluated, there are some studies that have focused on the utility of bone scans (scintigraphy and PET) to assess the response and toxicity associated with this therapy (36)(37)(38). In recent years, PSMA PET/CT has been making ground-breaking changes in the diagnosis and staging of PC patients, and this imaging modality is superior to choline PET (16,18,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the ALP value are often used as a marker for treatment follow-up, because ALP may reflect the extent of bone disease more accurately than PSA levels (38). In the ALSYMPCA trial, a significantly higher proportion of patients showed a response according to the ALP level in the 223 Ra group than in the placebo group ($30% reduction, P , 0.001).…”
Section: Discussionmentioning
confidence: 99%